Implementation of Preparation of Financial Statements Based on the Interpretation of Financial Accounting Standards No 35 At the Gereja Katolik Santo Yosep Pelindung Pekerja Manado - Dionesius Ambalinggi; Herman Karamoy; Victorina Tirayoh (PT FORMOSA CENDEKIA GLOBAL, 2023)
Interpretation of financial accounting standards no. 35 is a standard that regulates the presentation of financial statements of non-profit oriented entities which include the Catholic Church. 35. The research method used in this research is descriptive qualitative. The research results obtained that the format of financial reports at the Catholic Church of Santo Yosep Protector of Manado Workers is not in accordance with the Interpretation of Financial Accounting Standards No. 35. Presentation of financial reports at the Catholic Church of Santo Yosep Protector of Manado Workers still follows the 2019 Manado Diocese Parish Finance Manual. So, the Santo Joseph Catholic Church, Protector of Manado Workers, needs to make adjustments and be able to apply this Interpretation of Financial Accounting Standards No. 35 when the church prepares their financial reports, if in the 2019 Manado Diocese Parish Financial Guidelines there is this Interpretation of Financial Accounting Standards No. 35.